Implementing tri hita karana values in Grand Inna Kuta’s corporate social responsibility program - Bibit Bintang Bithara; I Putu Krisna Arta Widana; Ni Gst Nym Suci Murni (International Journal of Green Tourism Research and Applications, 2020)
Purpose: This research was conducted to know the implementation of corporate social responsibility activities at Grand Inna Kuta hotel, which is focused on the implementation corresponding to international regulation, national regulation, and local regulation concerning of corporate social responsibility (CSR). Research methods: By using descriptive qualitative method, this research describes CSR activities which refer to world tourism code of ethics, Indonesian republic government regulation, and local regulation which is the last in its relation with local culture i.e. Tri Hita Karana. Results and discussion: The result shows that there are 6 corporate social responsibility activities which conducted by Grand Inna Kuta namely; blood donor activity, beach cleaning activity, trees plant activity, tribute to the village, social assistance, and social assistance during Covid 19 pandemic. Conclusion: All the activities are a reflection of the local culture theory Tri Hita Karana which means harmonic relationship between human and God, human and human, and human and ecology.